Isolation and identification of new lactobacilli from goatling stomach and investigation of reuterin production in Lactobacillus reuteri strains - Kiňová Sepová, Hana; Bilková, Andrea (Folia microbiologica, 2013)
Five new strains of lactobacilli isolated from goatling's stomach were identified by molecular-biological approaches. Profiles of fermentable saccharides, Gram staining, and cell morphology were also determined. They were identified as Lactobacillus reuteri (strains KO4b, KO4m, KO5) and as Lactobacillus plantarum (strains KG1z, KG4). In DNA samples of all newly isolated L. reuteri strains as well as in L. reuteri E (Lreu E; originated from lamb), the part of gldC gene, coding large subunit of glycerol dehydratase, that is necessary for 3-hydroxypropionaldehyde (3-HPA; reuterin) production, was amplified using two designed primer sets. However, the 3-HPA production was revealed only in the strain Lreu E. It produced five- or ten-fold lower amount of 3-HPA in comparison with probiotic L. reuteri ATCC 55730 in aerobic or anaerobic conditions, respectively. Moreover, Lreu E completely lost its production ability after ca. five passages in MRS medium. The co-incubation of Lreu E, but not other L. reuteri isolates, with Escherichia coli re-induced 3-HPA production. In the case of L. reuteri ATCC 55730, the 3-HPA production increased more than four times after co-incubation with E. coli.
Keywords: kozy; Stomach; Propane; Animals; glyceraldehyd; Goats; Limosilactobacillus reuteri; zvířata; propan; žaludek; Glyceraldehyde; Lactobacillus